Zinc Oxide and Tungsten Trioxide Photocatalysts for Acetaminophen Removal in Water - Atiq Zainudin, Muhammad Izuan; Mokhtar, Hamizah; A. Halip Khalid, Azianabiha; Mustaffa, Nur Kamaliah; Zadariana Jamil (International Journal of Integrated Engineering, 2026)
Untreated Acetaminophen in water is chemically stable and hard to biodegrade. Ozone, ultrasounds, photoelectrochemical oxidation, active carbon adsorption, membrane filtration, and microorganism biodegradation are used to remove Acetaminophen from water. All these methods are effective, but they have drawbacks like incomplete Acetaminophen waste removal, harmful metabolic intermediates, increased water pollution, and the need for additional treatment to remove secondary wastes. Photocatalysis, utilizing light and semiconductors, efficiently removes most wastewater contaminants by decomposing organic compounds. In this study, ZnO, tungsten trioxide (WO3) and combinations of both were investigated as photocatalysts to degrade Acetaminophen in water. The degradation efficiency was investigated using a glass photoreactor with a working volume of 100 mL and assisted by UV light. Operating parameters, including initial Acetaminophen concentration and photocatalyst dosage, were also studied. The degradation of Acetaminophen was measured using a UV-Vis spectrophotometer. ZnO (80%) shows superior photocatalytic activity for Acetaminophen degradation in water compared to WO3 (3.45%) and their composites (Z1W1, Z1W3, Z3W1). Adding ZnO into WO3 enhances its photocatalytic activity and Acetaminophen degradation efficiency compared to only WO3 as a photocatalyst. The optimal degradation of Acetaminophen in water was achieved at an initial Acetaminophen concentration of 10 mg/L and photocatalyst dosage of ZnO at 0.1g with a degradation efficiency of 92%. Therefore, this proved that ZnO exhibits superior photocatalytic activity in degrading Acetaminophen in water.